Assessing and managing thermoregulatory responses to heat loss: a research journey - Holtzclaw, Barbara J. (Henry Stewart Talks, 2017)
Thermoregulatory factors that stimulate shivering, Common severity scale to record physiological consequences of shivering, Metabolic & cardiorespiratory effects of shivering after cardiac surgery with cardiopulmonary bypass, Surface cooling shivering prevention